Improving Teachers' Pedagogical Competence in Developing Project Modules in the Implementation of the Independent Curriculum at MTsN 1 Baubau - Nurul Hafidzah Asra; Yaya Suryana (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
Increasing teacher competence in developing project modules on the independent curriculum at MTsN 1 Baubau resulted in a module design that took the theme of local wisdom with the sub-theme